Characterisation of Malaysian agarwood species (aquilaria malaccensis, aquilaria hirta, and aquilaria beccariana) based on volatile chemical profile and somatic embryogenesis development - Mohd Syafik, Mohamad Hamdan (2022)
Aquilaria malaccensis, Aquilaria hirta, and Aquilaria beccariana are known as Malaysian agarwood species. They produce unique resinous wood and essential oil used in perfumery, medicinal, cosmetic and religious ceremony. It is difficult to identify the species accurately since there is no standard to represent the chemical compounds of agarwood and essential oil. This study aims to characterise the morphology of A. malaccensis, A. hirta and A. beccariana via scanning electron microscopic analysis, and to identify the volatile chemical compounds of the wood and the essential oil using Gas Chromatography-Flame Ionisation Detector and Gas Chromatography-Mass Spectrometry analyses. Then, somatic embryogenesis study was developed by optimising callus induction techniques using Scanning Electron Microscope (SEM) and Polymerase Chain Reaction (PCR) analysis. A. hirta was identified by the presence of hirsute on the abaxial side of leaves and midrib. The FESEM analysis shows plant vessel pits cannot be seen in the resinous wood images due to resin and microorganisms coverage. Interestingly, A. beccariana has simple vessel pits structure while A. hirta has nonvestured vessel pits with slit-like outer pit apertures. A total of 19 compounds were identified in resinous A. hirta wood consists of 5.97 % sesquiterpenes and 20.32 % sesquiterpenoid. There were 35 compounds found in A. hirta oil contained 0.45 % monoterpenes, 23.51 % sesquiterpenes and 19.53 % sesquiterpenoid. A total of 35 compounds were identified in resinous A. beccariana wood consists of 1.5 % monoterpenes, 15.27 % sesquiterpenes and 50.69 % sesquiterpenoid. There were 32 compounds found in A. beccariana oil contained 36.69 % sesquiterpenes and 49.58 % sesquiterpenoid. The highest frequencies of callus induction were observed on MS medium supplemented with BAP and NAA together with optimized growth parameters. SEM analysis showed embryogenic characteristics in cells of the yellow friable calli evidenced by the presence of small and isodiametric cells. Only SERK gene was successfully amplified and enable to proceed to in silico analysis. This study provides a reference for Malaysia agarwood species identification specifically for A. malaccensis, A. hirta and A. beccariana based on morphology evaluation and volatile chemical compounds profile of the essential oil and chip wood towards standardizing the quality. In addition, the somatic embryogenesis study provides fundamental results for genetic conservation effort of Aquilaria sp. towards more systematic and productive agarwood plantation in Malaysia.